Audit Syariah Sektor Awam (ASSA): Isu dan Cabaran - Mustafa Mohd Hanefah; Muhammad Iqmal Hisham Kamaruddin; Zurina Shafii; Supiah Salleh; Nurazalia Zakaria; Hairul Nizam Yusoff (Universiti Sains Islam Malaysian, 2024)
Page : 25-30